Perbandingan Metode Kolostrum dan Metode Terbuka Terhadap Lama Pelepasan Tali Pusat pada Bayi Baru Lahir - Ruri Yuni Astari; Dinda Nurazizah (Universitas Faletehan, 2019)
Umbilical cord care is the treatment and binding of the umbilical cord which causes the last physical separation between the mother of the baby, then the umbilical cord is treated in a sterile, clean, dry and protected from umbilical cord infection. The umbilical cord treatment method effectively speeds up the release of the umbilical cord and reduces the incidence of infection. This study aims to compare the length of umbilical cord release with the colostrum method and the open method in the process of releasing newborn umbilical cord. This type of research uses the experiment of static group comparism. The sample of this study was 30 newborns divided into 2 groups, 15 respondents in the intervention group and 15 respondents in the control group. The results showed that the timing of umbilical cord separation with the colostrum method was <5 days (fast category) and none had >7 days (slow category). Meanwhile, the timing of umbilical cord separation with the open method was <5 days (fast category) and the cord was fallen off >7 days (slow category). The statistical test results show that the length of the umbilical cord release for newborns with the colostrum method is about 4 days 9 hours faster than the open method with the results of the statistical test (ρ = 0.022). Health workers need to get information about cord care with the colostrum method so that it can be applied to newborns.